Sustainability in developing yarns woven antipyretic: use of kapok (ModaPalavra e-periódico, 2013)
The object of this study is the fiber coming from the Brazilian Kapok tree native. Thus, the focus of the research was to develop yarn using this fiber. For the development of this study, we used literature search of related issues stemmed from the kapok tree kapok, and other natural and chemical fibers; Experimental research; Reports test workshop. The results showed that kapok has antithermic property, and way be used in developing yarns. However, for this purpose, the fiber needs to be blended with another fiber too long also possesses antithermic property, so that product the end no loss pattern such characteristic. For this study, the test was carried out with the sleep wool through this merger, enabled the construction of the wire.
Keywords: yarn; antithermic; sustainability